Student Motivation And Learning Attitudes Toward Digital-Based Arabic Language Learning - Nurul Fahmi; Arif - Widodo; Alfina Nuris Sa'adah; Eli Safitri (STIQ Amuntai, 2026)
This study aims to analyse the levels of students’ learning motivation and learning attitudes toward digital-based Arabic language instruction, and to examine the relationship between the two variables. The research employs a quantitative, descriptive-correlational design. The study subjects are 29 second-semester students of the Arabic Language Education Program at Sunan Drajat University, selected using a total sampling technique. The research instruments include questionnaires measuring learning motivation and learning attitudes, utilising a Likert scale. Data analysis is conducted using descriptive statistics and the Pearson Product-Moment correlation. The results indicate that students’ learning motivation falls into the high category (mean = 5.00), while their learning attitudes are categorised as positive (mean = 4.99). The correlation test yields r = 0.68 (p < 0.05), indicating a significant relationship between learning motivation and learning attitudes. This study demonstrates that digital-based Arabic language instruction can positively enhance students’ motivation and attitudes toward learning.